ANALYSIS OF THE ROLE OF TRANSFORMATIONAL LEADERSHIP IN IMPLEMENTING ORGANIZATIONAL STRATEGY - Ahmad Burhanudin (Sean Institute, 2023)
Transformational leadership is known as a leadership style that is able to inspire, motivate and facilitate positive change in an organization. Transformational leadership focuses on the leader's ability to encourage innovation, build an adaptive organizational culture, and improve team performance . Therefore, this research aims to analyze the role of transformational leadership in implementing organizational strategy. This research uses a qualitative approach with descriptive methods. The research results show that transformational leadership is very important in implementing organizational strategy because it motivates and inspires teams to adapt and innovate. Transformational leaders create a strong vision, encourage creativity, and build trust, so that organizational strategies are not just plans on paper, but are also implemented in daily practice. With a focus on individual development and team empowerment , this leadership style improves motivation, communication, and company performance, supports efficiency, innovation, and a positive work culture, and helps achieve long-term goals and organizational sustainability amidst market changes.